Microstructural Characterization of Fibre Reinforced Polymer (FRP) Composite (Kenaf Fibre and Polyester Resin) for Structural Applications - PYENDANG, Zachariah S.; ACHEMA, Felix; YAKUBU, Isheni; APEH, Solomon E. (FUDMA Journal of Engineering and Technology, 2026)
Demand for sustainable, high-performance construction materials has driven interest in natural fibre–reinforced polymer (NFRP) composites. This study characterizes microstructure and thermal behaviour of polyester composites reinforced with powdered kenaf fibre at 0, 10, 20, 30 and 40 wt%. Composites were fabricated under controlled conditions and analyzed by FTIR, XRD, TGA/DTG, SEM and EDX to evaluate chemical interactions, crystallinity, thermal stability and morphology. FTIR identified hydroxyl, carbonyl and aromatic functional groups, indicating interfacial interactions between kenaf and polyester. XRD showed increasing crystallinity with higher fibre loading, implying greater structural ordering. TGA/DTG revealed enhanced thermal stability at moderate fibre contents, with optimal performance around 20–30 wt%, while stability declined at 40 wt%. SEM of pounded kenaf confirmed irregular, short fibres with rough fractured ends; untreated fibres showed surface impurities and relatively smooth areas consistent with partial hemicellulose and lignin removal. SEM of composites at 10 wt% displayed effective load transfer and strong kenaf–resin bonding. In contrast, composites with 20–40 wt% exhibited numerous fibre pull-outs, long pull-out lengths, interfacial gaps, poor wetting and weak adhesion, indicating diminished interfacial bonding at higher loadings. EDX quantified elemental composition of kenaf fibres (64.01% C, 34.05% O, 1.13% K, 0.30% S, 0.27% Ca, 0.24% Mg), confirming the presence of mineral elements that may influence composite behaviour. Overall, incorporation of kenaf significantly affects the chemical structure and thermal response of polyester composites. Results suggest an optimal kenaf content range (approximately 20–30 wt%) balancing improved crystallinity and thermal resistance with acceptable interfacial performance. These findings support the potential of kenaf–polyester composites as eco‑friendly, cost‑effective materials for structural applications, and provide guidance for their development in engineering and construction.